Prospective comparison of three methods for detecting peri‐operative neurocognitive disorders in older adults undergoing cardiac and non‐cardiac surgery. (11th January 2023) - van Zuylen, M. L.; Kampman, J. M.; Turgman, O.; Gribnau, A.; ten Hoope, W.; Preckel, B.; Willems, H. C.; Geurtsen, G. J.; Hermanides, J.
Summary: Postoperative neurocognitive disorders occur frequently in older adult patients. Neuropsychological assessment is the gold standard for diagnosis, but the resources required for routine use are significant. Instead, it is common for simplified and unvalidated tests to be used for trials and in clinical practice. We undertook a single‐centre prospective observational study in elective surgical patients aged ≥ 65 years recruited between September 2019 and January 2021. Patients underwent neuropsychological assessment, the Modified Telephone Interview for Cognitive Status and Montreal Cognitive Assessment before surgery. Tests were repeated at approximately four to eight postoperative weeks. We included 105 patients and 28 (27%) were lost to follow‐up. Pre‐operative Modified Telephone Interview for Cognitive Status and cognitive domain scores were very weakly to moderately correlated (r = 0.09–0.41). Pre‐operative Montreal Cognitive Assessment and cognitive domain scores were very weakly to weakly correlated (r = 0.17–0.37) Postoperative Modified Telephone Interview for Cognitive Status and cognitive domain scores were very weakly to weakly correlated (r = 0.09–0.36). Postoperative Montreal Cognitive Assessment score and cognitive domain scores were very weakly to weakly correlated (r = 0.07–0.36). Overall, there was limited agreement between tests. We conclude that the Modified Telephone Interview for Cognitive Status and Montreal Cognitive Assessment should not be used in isolation to diagnose postoperative neurocognitive disorders. There seems to be little to no pre‐operative, postoperative or pre‐ to postoperative correlation between these tests and the neuropsychological assessment in older adults without pre‐operative cognitive impairment.